ORAL INTERACTION AROUND COMPUTERS IN THE PROJECT-ORIENTED CALL CLASSROOM - Gumock Jeon-Ellis; Robert Debski; Gillian Wigglesworth (Language Learning and Technology, 2005)
Language teachers need to provide students with a context for genuine communication (Sullivan, 2000). Project-oriented computer-assisted language learning (PrOCALL) attempts to achieve this by orienting learners towards tasks, which encourages them to communicate in the target language while working towards completion of a project (Debski, 2000). The study investigates the oral interaction that takes place in this context. According to Vygotsky, social interaction mediates cognitive development. Swain's (2000) application of this concept to language learning suggests that collaborative dialogues mirror the moments of language development. Using this framework, the present study identifies "language related episodes" (Swain & Lapkin, 1998) and describes the characteristics of the oral interaction generated by two small groups of French learners working towards the completion of Web pages in a major Australian university. The study also describes instances of "triadic interaction" (van Lier, 2002) involving learners' interactions with each other and with the computer screen. In sum, the analysis suggests that the PrOCALL context can provide students with opportunities for collaborative dialogues, through which language learning occurs. However, the social context of these interactions is mediated by personal relationships, preferences, and motivations.